Elevation of Serum Total Prostate-Specific Antigen (PSA) Level as Predictor of Prostate Cancer (PCa) of Patient Following Transurethral Resection of Prostate (TURP) - Muhammad Sidiq; Trisula Utomo; Wikan Kurniawan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Prostate cancer (PCa) is a significant global health issue, particularly in aging populations. In Indonesia, it is the fifth most common cancer. Diagnosis is often complicated by benign prostatic hyperplasia (BPH), which also elevates Prostate-Specific Antigen (PSA), limiting its specificity. This study aimed to establish an optimal preoperative PSA cutoff and assess the predictive utility of PSA, Neutrophil-Lymphocyte Ratio (NLR), and PSA Density (PSAD) for detecting PCa in patients undergoing Transurethral Resection of the Prostate (TURP). A retrospective cohort study analyzed 152 patients undergoing TURP at Gadjah Mada University Hospital (May 2018-July 2024) using a consecutive sampling method. Preoperative serum Total PSA, NLR, and PSAD were evaluated against postoperative histopathology. Bivariate and multivariate logistic regression were used to analyze relationships, while Receiver Operating Characteristic (ROC) curve analysis determined the optimal PSA cutoff. Prostate cancer was diagnosed in 19.1% of patients (n=29). ROC analysis identified a preoperative PSA cutoff of >19.95 ng/mL for predicting PCa, yielding an Area Under the Curve (AUC) of 0.863, with 75.9% sensitivity and 75.6% specificity. The multivariate analysis confirmed that elevated preoperative PSA (Odds Ratio [OR] 3.648), NLR (OR 3.868), and PSAD (OR 9.553) were all significant independent predictors of a PCa diagnosis. Among these, PSAD emerged as the strongest predictive marker. Preoperative serum PSA, NLR, and PSAD are valuable independent predictors for PCa in patients undergoing TURP for symptomatic BPH. A PSA cutoff of >19.95 ng/mL is a clinically relevant diagnostic threshold for this specific population. Employing a multi-marker panel, with particular emphasis on PSAD, can enhance risk stratification and help clinicians identify high-risk patients warranting further investigation for PCa when planning a TURP procedure.Keywords: Prostate Specific Antigen (PSA), Prostate Cancer (PCa), Benign Prostate Hyperplasia (BPH), Transurethral Resection of The Prostate (TURP)